Sexual Function After Hypofractionated Versus Conventionally Fractionated Radiotherapy for Prostate Cancer: Results from the Randomized Phase III HYPRO Trial. Issue 11 (1st November 2016) - Wortel, Ruud C.; Pos, Floris J.; Heemsbergen, Wilma D.; Incrocci, Luca
ABSTRACT: Introduction: Hypofractionated radiotherapy could increase the radiobiological tumor dose for localized prostate cancer. The effects of hypofractionation on sexual function are not well known. Aim: To compare sexual function in patients with prostate cancer treated with 78 Gy in 39 fractions of 2 Gy or 64.6 Gy in 19 fractions of 3.4 Gy. Methods: In total, 820 men with intermediate- to high-risk T1b-T4NX-0MX-0 prostate cancer were enrolled in the phase III HYPRO trial (2007–2010) and randomized to conventional fractionation (39 × 2 Gy) or hypofractionation (19 × 3.4 Gy). Sexual function was assessed at baseline and at 6, 12, 24, and 36 months after treatment using the International Index of Erectile Function (IIEF). For this analysis, patients (n = 322) with a baseline assessment, at least one follow-up assessment, and no or short-term (6-month) androgen-deprivation therapy were included. Main Outcome Measures: Mean IIEF domain scores were compared between treatments in the total population and the hormone-naïve population (n = 197) using the independent t-test. Incidences of severe erectile dysfunction (domain score < 11) at last follow-up were calculated in patients with partial or full baseline function. Binary logistic regression analyses were applied to calculate the odds ratio of hypofractionation vs conventional fractionation and to adjust for clinical factors. Results: Median age was 71 years (interquartile range = 67–71) and median follow-up was 37 months (interquartile range = 25–38). Androgen-deprivation therapy was prescribed in 125 (39%). IIEF domain scores decreased after treatment but were comparable between treatment arms at baseline and during follow-up. Orgasmic function scores in hormone-naïve patients were significantly higher at 3 years after hypofractionation (4.08 vs 2.65, P = .031). In patients (n = 120) with partial or full baseline erectile function, the incidence of erectile dysfunction at last follow-up was 34.4% for hypofractionated treatment vs 39.3% for conventional treatment (adjusted odds ratio = 0.84, 95% CI = 0.37–1.90, P = .67). Conclusion: No significant differences in erectile functioning between conventional and hypofractionated radiotherapy were found. Hormone-naïve patients reported significantly higher orgasmic function scores at 3 years after hypofractionation.